ENHANCING MATERNAL NURSING VIA VISUAL THINKING (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Visual thinking strategy, in turn, consists of a number of techniques and methods that help people visualize their thoughts, feelings, and ideas. This strategy is often used in the educational process, as well as in the fields of health and care. The importance of visual thinking strategy is especially high in maternal and women's health care. This article focuses on a quasi-experimental study to study the role of visual thinking strategy in maternal and women's health care and its effectiveness.